HUMOROUS ASPECTS OF TRUCK CONTAINER SIGNS IN INDONESIA - Wijana, I Dewa Putu (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
As Homo Ludens, human beings inherently possess a penchant for play. They exhibit the remarkable ability to craft various forms of playful devices, one of which revolves around the skillful use of language as their primary vehicle for verbal communication. This paper explores the humorous dimensions inherent in language usage, as artfully harnessed in the signage adorning truck containers. By meticulously scrutinizing these container signs displayed on trucks navigating the highways of Indonesia, this study unveils that the creators of these signs employ three fundamental mechanisms, as articulated by Bergson's (1983) theory, to elicit smiles and laughter from their audience. These mechanisms encompass repetition, inversion, and, most notably, the concept of reciprocal interference within series. Such effects are achieved through various techniques, including phonological alterations, ambiguities, juxtapositions, and the deliberate incorporation of taboos and insults.